Divergent roles of p120‐catenin isoforms linked to altered cell viability, proliferation, and invasiveness in carcinogen‐induced rat skin tumors. Issue 7 (6th March 2017) - Wang, Rong; Chen, Ying‐Shiuan; Dashwood, Wan‐Mohaiza; Li, Qingjie; Löhr, Christiane V.; Fischer, Kay; Ho, Emily; Williams, David E.; Dashwood, Roderick H.
Abstract : The heterocyclic amine 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐ b ]pyridine (PhIP) targets multiple organs for tumorigenesis in the rat, including the colon and the skin. PhIP‐induced skin tumors were subjected to mutation screening, which identified genetic changes in Hras (7/40, 17.5%) and Tp53 (2/40, 5%), but not in Ctnnb1, a commonly mutated gene in PhIP‐induced colon tumors. Despite the absence of Ctnnb1 mutations, β‐catenin was overexpressed in nuclear and plasma membrane fractions from PhIP‐induced skin tumors, coinciding with loss of p120‐catenin from the plasma membrane, and the appearance of multiple p120‐catenin‐associated bands in the nuclear extracts. Real‐time RT‐PCR revealed that p120‐catenin isoforms 1 and 4 were upregulated in PhIP‐induced skin tumors, whereas p120‐catenin isoform 3 was expressed uniformly, compared with adjacent normal‐looking tissue. In human epidermoid carcinoma and colon cancer cells, transient transfection of p120‐catenin isoform 1A enhanced the viability and cell invasion index, whereas transient transfection of p120‐catenin isoform 4A increased cell viability and cell proliferation. Knockdown of p120‐catenin revealed a corresponding reduction in the expression of β‐catenin and a transcriptionally regulated target, Ccnd1/ Cyclin D1. Co‐immunoprecipitation experiments identified associations of β‐catenin with p120‐catenin isoforms in PhIP‐induced skin tumors and human cancer cell lines. The results are discussed in the context of therapeutic strategies that might target different p120‐catenin isoforms, providing an avenue to circumvent constitutively active β‐catenin arising via distinct mechanisms in skin and colon cancer.